Referenzmodell zur Beschreibung der Geschäftsprozesse von After-Sales-Dienstleistungen unter besonderer Berücksichtigung des Mobile Business - Gajewski, Tobias

Ein Beitrag zur klassifizierenden Modularisierung von Verfahren für die Produktionsplanung - Rüther, Michael

Abschätzung des Ressourcenbedarfs von hochintegrierten mikroelektronischen Systemen - Langen, Dominik

Consensus in WSN – Identifying critical protocol mechanisms - Köpke, A.; Karl, Holger; Wolisz, A. (GI / ITG Fachgespräche Drahtlose Sensornetzwerke)

Entgeltflexibilisierung im Europäischen Binnenmarkt - Krimphove, Dieter (Internationales Entgeltmanagement)

Wettbewerbssicherung kleiner und mittelständischer Unternehmen durch Zugangsberechtigung zu fremden Betriebs- und Produktionsmitteln Eine ökonomischen Analyse der „essential-facility“-Doktrin im US-amerikanischen, europäischen und deutschen Recht - Krimphove, Dieter (Management der Forschung und Entwicklung sowie der Technologiekooperation in kleinen und mittleren Unternehmen)

Spieltheoretische Aspekte des Rechts – Ein Beitrag zur Analyse und Gestaltung von Recht mit Hilfe objektiver quanitvizierbaren Methodik – - Krimphove, Dieter (Rechtstheorie)

Der Kündigungsschutz im Europäischen Arbeitsrecht - Krimphove, Dieter (TÜRKIYE & ENDÜSTRI ILIŞKILERI)

Das Recht der Unternehmensfinanzierung - Krimphove, Dieter; Welp, Jürgen (Handbuch: Krisen- und Insolvenzmanagement)

Data Distribution Algorithms for Storage Networks - Salzwedel, Kay

The Ising Model: Simple Evolutionary Algorithms as Adaptation Schemes - Briest, Patrick; Brockhoff, Dimo; Degener, Bastian; Englert, Matthias; Gunia, Christian; Heering, Oliver; Jansen, Thomas; Leifhelm, Michael; Plociennik, Kai; Röglin, Heiko; Schweer, Andrea; Sudholt, Dirk; et al. (Parallel Problem Solving from Nature - PPSN VIII)

Experimental Supplements to the Theoretical Analysis of EAs on Problems from Combinatorial Optimization - Schweer, Andrea; Leifhelm, Michael; Degener, Bastian; Heering, Oliver; Tannenbaum, Stefan; Röglin, Heiko; Gunia, Christian; Englert, Matthias; Briest, Patrick; Sudholt, Dirk; Brockhoff, Dimo; Wegener, Ingo; et al. (Parallel Problem Solving from Nature - PPSN VIII)

Dokumentationsschrift zum Paderborner Grundschultag 2003 - Büker, Petra (Interkulturell lernen – erziehen – bilden (Paderborner Beiträge zur Unterrichtsforschung und Lehrerbildung, Bd. 8))

A case for virtualized arrays of RAID - Brinkmann, André; Salzwedel, Kay; Vodisek, Mario (Proceedings of the international workshop on Storage network architecture and parallel I/Os - SNAPI '04)
Redundant arrays of independent disks, also called RAID arrays, have gained a wide popularity in the last twenty years. Most of the disks used in the server market are currently based on RAID technology. The primary reason for introducing RAID technology in 1988 has been the fact that large disk systems have become much slower and more expensive than the connection of a large number of inexpensive disks and the use of them as an array. The times seem to repeat themselves. Today, large scale RAID arrays have become incredible big and expensive. It seems that it makes sense to replace them by a collection of smaller and inexpensive arrays of JBODs or mid-ranged RAID arrays. In this paper we will show that combining these systems with state-of-the-art virtualization technology can lead to a system that is faster and less expensive than an enterprise storage system, while being as easy to manage and as reliable. Therefore we will outline the most important features of storage management and compare there realization in enterprise class storage systems and in current and future virtualization environments.

The design of PaMaNet the Paderborn mobile ad-hoc network - Schindelhauer, Christian; Böttcher, Stefan; Rammig, Franz (Proceedings of the second international workshop on Mobility management & wireless access protocols)
Wireless connectivity is state of the art for local area networks. Currently, most W-LAN networks rely on a centralized design with access points routing all inner and outbound traffic. These access points are intrinsic communication bottlenecks. Mobile Ad Hoc Networks (MANET) overcome this problem, because every participant works as well as a simple node and as a router. Current MANETs are restricted in scalability, because they rely on flooding mechanisms or complete routing tables. Other approaches, providing better scalability use clustering, yet network performance deteriorates in case of high node mobility. We describe the design of a PAMANET, the Paderborn Mobile Ad Hoc Network, a MANET overcoming these problems providing scalability and reliability in a mobile scenario. When implemented, PAMANET works with standard W-LAN IEEE 802.11 radio devices, provides IPv6 communication interfaces and works on personal computers under a standard Linux distribution. First, we present current routing protocols and classify them with respect to scalability and stability in dynamically evolving MANETs. Then, we discuss related research in the area of distributed hash tables and consistent hashing, used for relieving hot spots in the Web, storage area networks and peerto-peer networks, which inspires the design of PAMANET. PAMANET consists of three main components: First, the embedding of the routing layer into IEEE 802.11 and IPv6 by using techniques used at the ad hoc support library (aslib) by Gupta et al. Second, the routing layer which combines a landmark routing, hierarchical clustering, consistent hashing for providing location dependent addresses and lookup-service for the location of nodes. Third, a peerto-peer data storage system based on egoistic distributed caches enabling hop and traffic efficient data access on replicated data partitions. The routing layer incorporates a variety of new approaches. Link distances reflect the failure probability of links, which is estimated by the reciprocal age of the link. Then, we combine a landmarking system on this metric with the hierarchical layer graph yielding small landmark addresses and small routing tables. To balance the load of the distributed lookup-service for landmark addresses, a hierarchical weighted consistent hashing scheme is used. This ensures that each node receives an equal part of all landmark addresses. Using these mechanisms (regularly and on demand) PAMANET adjusts IPv6 routing tables such that short stable routes are preferred. For the distribution of control data like landmark information PAMANET uses a message box system interface to provide fast one-hop communication. On top of this system, PAMANET provides a peer-to-peer data storage and lookup system that realizes time, traffic, and load efficient access using egoistic caches and data segmentation strategies.

Virtualization with prefetching abilities based on iSCSI - Bleckmann, Peter; Schomaker, Gunnar; Slowik, Adrian (Proceeding of International Workshop on Storage Network Architecture and Parallel I/O)
The Internet-SCSI protocol [iSCSI] allows a client to interact with a remote SCSI-capable target by means of block-oriented commands encapsulated within TCP/IP packets. Thereby, iSCSI greatly simplifies storage virtualization, since clients can access storage in a unified manner, no matter whether the I/O-path is short or long distance. Intermediate devices located on the path between a client and a target can easily intercept iSCSI sessions and rewrite packets for the sake of load balancing, prefetching, or redundancy, to mention just a few beneficial applications. Within this paper we describe the design and implementation of such an iSCSI capable intermediate device that deploys prefetching strategies in combination with redundant disks to reduce average I/O-latency. Depending on its location within the network, this virtualization and prefetching device can hide wide area access latency and reduce network contention targeting remote SCSI-devices to a large extent.

Point Cloud Surfaces using Geometric Proximity Graphs - Klein, Jan; Zachmann, Gabriel (Computers and Graphics)

Proximity Graphs for Defining Surfaces over Point Clouds - Klein, Jan; Zachmann, Gabriel (Eurographics Symposium on Point-Based Grahics (SPBG'04))

Nice and Fast Implicit Surfaces over Noisy Point Clouds - Klein, Jan; Zachmann, Gabriel (SIGGRAPH 2004, Sketches)

Point Cloud Collision Detection - Klein, Jan; Zachmann, Gabriel (Computer Graphics Forum (Proceedings of EUROGRAPHICS 2004))